Fracture mechanics analysis methods - Liang, Yue (2017)
The objective of this project is to develop fracture mechanic analysis methods and computerize the calculation procedure. In this study, analysis was conducted in MATLAB environment. In this paper, the stress intensity factor in plain plate developed by Newman and Raju was first discussed and followed by study of the stress intensity magnification factor Mk in T-butt joint standardized in BS 7910:2013. A program was then developed in MATLAB to analyse the relationship between Mk and a/T ratio. Furthermore, the calculated Mk factor was then applied for prediction of fatigue crack propagation under membrane loading. Based on simulation result, the predicted fatigue life in plate with attachment was significantly reduced than in plain plate. And finally, a graphical user interface was developed in MATLAB to facilitate the evaluation.